Techniques Used by Coaches to Influence Referees in Professional Team Handball - Thierry, D. (International Journal of Sports Science and Coaching, 2014)
This study is based on persuasion models (Elaboration Likelihood Model; Heuristic Model of Persuasion) and Goffman's dialogic communication approach. It focuses on the means coaches use to influence referees' decision-making during games, and seeks to identify the contextual factors (game period, opposing team, coach yellow cards) that impact the influence processing used. Influence processing is examined through an analysis of the content of the verbal and behavioral communication of professional male coaches (n = 3) recorded during 14 games through deductive then inductive approaches. The results show that: 1) contextual factors have an effect on influencing decision-making and communicating disagreements about game situations; 2) coaches use technical skills more than any other means to influence referees; and 3) during the halftime break, the coaches make argued criticisms of referees' interpretation of play, while during play, coaches can influence referees' interpretation through direct speech not requiring arguments.